2020
DOI: 10.1587/elex.17.20200036
|View full text |Cite
|
Sign up to set email alerts
|

A low-power high-output-efficiency bipolar Colpitts VCO using base inductive feedback and Q-factor enhancement for analog signal acquisition

Abstract: A low-power Colpitts VCO with high output efficiency that uses base inductive feedback and Q-factor enhancement techniques is proposed in this paper. The base inductive feedback technique employs an inductor at the base of the bipolar transistor to generate a feedback enhancement effect and reduce the start-up current. The Q-factor enhancement technique adopts a capacitor voltage divider at the output of the Colpitts VCO to improve the DC-to-RF efficiency. The mechanisms are theoretically analyzed, and then a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The architecture of the proposed VCO is based on the Colpitts structure studied in the references [16][17][18] and the structure proposed by the authors in [12] as shown in Figure 2. The active part of this oscillator consists of two transistors pHEMT 1 and pHEMT 2: each one has 4 fingers and a gate length and width of 0.25 µm and 20 µm, respectively.…”
Section: Voltage Controlled Oscillator Circuitmentioning
confidence: 99%
“…The architecture of the proposed VCO is based on the Colpitts structure studied in the references [16][17][18] and the structure proposed by the authors in [12] as shown in Figure 2. The active part of this oscillator consists of two transistors pHEMT 1 and pHEMT 2: each one has 4 fingers and a gate length and width of 0.25 µm and 20 µm, respectively.…”
Section: Voltage Controlled Oscillator Circuitmentioning
confidence: 99%